Metformin use in gestational diabetes: Awareness, attitude, and practice among healthcare professionals in Malaysia - Nur Aizati Athirah Daud; Syed Ghouse Mohiuddin; Yi Ping Ong; Faridah Yusof; Fadhleena Yusoff; Sabariah N Harun; Siti Maisharah S. Ghadzi (Wolters Kluwer Medknow Publications, 2021)
Background: Metformin has been added in the Malaysian clinical practice guideline (CPG) as one of the first-line options in the management of gestational diabetes mellitus (GDM); however, the uptake on this practice among healthcare professionals is unknown. Objective: The objective of the study is to determine the awareness, attitude, and practice and their predictors on the use of metformin for GDM among healthcare professionals in Malaysia. Materials and Methods: This was a multicenter, cross-sectional study in three tertiary hospitals in Malaysia. Medical doctors and pharmacists working in several departments were invited to participate in a survey using self-administered questionnaires. Results: From 350 questionnaires distributed, 225 were completed by medical doctors (43.1%), pharmacists (40.4%), and specialists (7.5%). Less than 30% of them were aware on the option of using metformin as one of the first-line agents in GDM. Education level, department, and profession were found to be associated with the awareness level (P = 0.016, P = 0.004, and P = 0.001, respectively). 70.2% of the respondents showed a positive attitude toward metformin use in GDM. Only 64 (28.4%) of the respondents have prescribed/dispensed metformin for GDM before, although more than half will consider doing so in the future. Having postgraduate qualifications increased the likelihood of having a good awareness (odds ratio [OR]: 2.44, 95% confidence interval [CI] 1.23-4.85) and to consider prescribing/dispensing metformin for GDM patients (OR: 2.27, 95% CI 1.08-4.78). Conclusion: Despite a positive attitude toward metformin use in GDM among healthcare professionals in Malaysia, their awareness level on this practice was low as they currently prefer the use of insulin over metformin.